A Simple and Efficient Synthesis of 3,4,5-Trisubstituted/N-Fused 1,2,4-Triazoles via Ceric Ammonium Nitrate Catalyzed Oxidative Cyclization of Amidrazones with Aldehydes Using Polyethylene Glycol as a Recyclable Reaction Medium - Nakka, Mangarao; Tadikonda, Ramu; Rayavarapu, Srinuvasarao; Sarakula, Prasanthi; Vidavalur, Siddaiah (Synthesis, 2015)
An environmentally benign protocol is described for the synthesis of 3,4,5-trisubstituted 1,2,4-triazoles and N-fused 1,2,4-triazoles via ceric ammonium nitrate catalyzed oxidative cyclization of amidrazones and aldehydes using polyethylene glycol as recyclable reaction medium. This protocol is effective toward various substrates having different functionalities. The easy recyclability of the reaction medium makes the process economic and potentially viable for commercial applications.
Keywords: polyethylene glycol; ceric ammonium nitrate; 1,2,4-triazoles; [1,2,4]triazolo[4,3-a]pyridines; [1,2,4]triazolo[4,3-a]pyrazines